2020
DOI: 10.1021/acs.jafc.0c00230
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Insecticidal Activity of Novel Doramectin Derivatives Containing Acylurea and Acylthiourea Based on Hydrogen Bonding

Abstract: Our recent investigation on the insecticidal activities of several doramectin derivatives preliminarily revealed that the presence of hydrogen bonds at the C4″ position of the molecule with target protein γ-aminobutyric acid (GABA) receptor was crucial for retaining high insecticidal activity. As a continuation of our research work on the development of new insecticides, two series of novel acylurea and acylthiourea doramectin derivatives were designed and synthesized. The bioassay results indicated that the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.jafc.1c03586. Physical characteristics and 1 H, 13 C, and 19 F NMR spectra of the title compounds (7a−7ab) (PDF)…”
Section: * Sı Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.jafc.1c03586. Physical characteristics and 1 H, 13 C, and 19 F NMR spectra of the title compounds (7a−7ab) (PDF)…”
Section: * Sı Supporting Informationmentioning
confidence: 99%
“…14−16 The importance of hydrogen bonding between bioactive molecules and target proteins has been widely demonstrated. 17,18 Thus, with the urea bridge being conserved, many modifications of the acyl and heterocyclic aryl moieties have resulted in rich biological activities for controlling insects, 19 fungi, 20 cancers, 21 tumors, 16 etc. The combination of urea and acyl groups remains a priority target for the creation of new agrochemicals.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al 90 synthesized and characterized a novel series of acyl thiourea derivatives of doramectin 112a–v Scheme 48 . Their biological assay and molecular docking studies showed them to be used as potential insecticides.…”
Section: Applicationsmentioning
confidence: 99%
“…Avermectins , represent a group of 16-membered macrolide lactones obtained by fermentation from Streptomyces avermitilis. , These compounds are generally used as a pesticide for the treatment of insect pests and parasitic worms due to their anthelmintic and insecticidal properties. , The main mechanism of avermectins is acting on γ-aminobutyric acid (GABA)-related chloride ion channels , unique to nematodes, insects, ticks, and arachnids. Owing to their remarkable biological activity and low mammalian toxicity, avermectins, also called natural product pesticides, have long been studied for commercial agricultural use around the globe, with China being the world’s largest producer of avermectins. Since their discovery, various studies , have been conducted to obtain novel derivatives with higher activity and lower toxicity by modifying avermectin B1a species such as ivermectin, emamectin benzoate, and selamectin (Figure ).…”
Section: Introductionmentioning
confidence: 99%